In vitro study of the effect of combinations of cereals and sugar beet pulp on pH and gas production pattern in concentrate or forage-based diets for ruminants - Amanzougarene Z.; Yuste S.; De Vega A.; Fondevila M. (Innovation for sustainability in sheep and goats, 2019)
The nature of the dietary carbohydrate fraction may affect fermentative conditions and performance, depending on rumen environment. Three mixtures (1:1 maize:barley, MB, and maize:sugarbeet pulp at either 1:1, MP, or 3:1, 3MP) were incubated in an in vitro semi-continuous culture system, using inoculum from lambs receiving a concentrate (CI) or a forage (FI) diet (three 24h series for each inoculum). Medium pH was poorly buffered from 0 to 6h, and allowed to rise around 6.5 from 8h onwards. With CI, minimum incubation pH was reached after 6h, being higher (P<0.05) with MP than with MB and 3MP from then (6.06, 5.97 and 5.95 at 6h, respectively) to 20h (6.78, 6.67 and 6.67). Gas production was highest for MB at 2h and from 6 to 16h, and lowest with 3MP from 2 to 8h, and with MP from 20h onwards (P<0.05), whereas no differences (P>0.05) were recorded neither between MB and 3MP at 20 and 24h, nor between MP and 3MP from 10 to 16h. With FI, pH was lower with MB than with 3MP at 6h (6.33 vs. 6.39, P<0.05), and maintained lowest onwards (P<0.05) with MB. The volume of gas from 3MP was lowest (P<0.05) up to 4h, and lower with 3MP than with MB from 6h onwards (P<0.05), whereas differences between MB and MP were only recorded after 24h. In both concentrate and forage environments, MP maintains a more stable pH pattern while fermentation was not noticeably depressed compared to higher starch proportions mixtures (MB and 3MP).
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)